2011
DOI: 10.1139/f2011-011
|View full text |Cite
|
Sign up to set email alerts
|

Do juvenile Atlantic salmon (Salmo salar) use chemosensory cues to detect and avoid risky habitats in the wild?

Abstract: We examined whether juvenile Atlantic salmon (Salmo salar) in the wild adjust their behaviour in response to chemical cues of predator activity during a 4-week period after emergence from gravel nests. In each of seven 75 m 2 sites in Catamaran Brook, New Brunswick, Canada, we established three contiguous sections differing in perceived predator activity by releasing stream water in control sections, conspecific alarm cues in risky sections, and nothing in buffer sections in both 2006 and 2007. As predicted, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The detection of chemical cues and signals by olfactory and gustatory receptors plays a central role in the decision-making process [22], especially in structurally complex or turbid environments or under low light conditions [23 -25]. For instance, homing [26,27], microhabitat choice [28,29], mate selection [30,31], kin recognition [32], food location [33], dominance interactions [34] and predator avoidance [35,36] are all mediated by the detection of chemical cues, at least to some extent. Any interference with the functioning of normal chemosensory responses could reduce the ability to perceive basic environmental stimuli or public information that is critical for long-term survival.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of chemical cues and signals by olfactory and gustatory receptors plays a central role in the decision-making process [22], especially in structurally complex or turbid environments or under low light conditions [23 -25]. For instance, homing [26,27], microhabitat choice [28,29], mate selection [30,31], kin recognition [32], food location [33], dominance interactions [34] and predator avoidance [35,36] are all mediated by the detection of chemical cues, at least to some extent. Any interference with the functioning of normal chemosensory responses could reduce the ability to perceive basic environmental stimuli or public information that is critical for long-term survival.…”
Section: Introductionmentioning
confidence: 99%
“…We found that none of the alarm cues induced a significant change in the distribution of the experimental animals in the laboratory stream channels. There is similar evidence from a study (Kim et al, 2011) that examined the responses of young-of-theyear (YOY) and 1+ Atlantic salmon (Salmo salar) presented regularly with conspecific damage-released alarm cues during a 4week period in a wild stream. The YOY S. salar changed their distribution in response to the conspecific alarm cue, resulting in a decrease of their density in the alarm cue sections and an increase of their density in the control and buffer sections.…”
Section: Resultsmentioning
confidence: 71%
“…In consequence, salmon density increased in adjacent control reaches as risk-averse fishes apparently emigrated from the experimental reaches (Kim et al 2011). Preferential occupation of less-risky habitats, often characterized by greater abundance of physical refugia, has been documented in several freshwater and marine fish species (Gotceitas and Brown 1993;Jordan et al 1997;Dupuch et al 2009).…”
Section: Discussionmentioning
confidence: 99%